Cahiers de prison : cahiers 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 - Gramsci, Antonio; Paris, Robert; Perrus, Claude; Laroche, Pierre ([Paris] : Gallimard, 1991)
Bibliotheek François Vercammen
Frans
Meerdelige publicatie